Nostalgia and the New Cosmopolitan: Literary and Artistic Interventions in the City of Casablanca - Katarzyna Pieprzak (Studies in 20th & 21st Century Literature, 2009)
In the past ten years, groups of local artists, architects, writers and activists have become concerned not only with the changing material conditions of Casablanca, but also with the city’s memory. This essay is concerned with two projects that reveal how nostalgic modes of recollection expose and limit geographies of cosmopolitan identity in the city. The first project, a collection of twelve booklets written by prominent novelists and poets with well-known photographers, is entitled Casablanca, fragments d’imaginaire. This collection argues that nostalgia and phantasm are key organizing concepts through which the city should be recollected, claiming that these modes of representation produce multiple, plural and heterogeneous forms and imaginations that allow the “soul” of the city to emerge. The second project is a participatory urban archeology art project started by the art collective La Source du lion. The collective practices a non-nostalgic curation of memory that moves cosmopolitanism in the city beyond a historical category into a contemporary practice and ethos. Read comparatively, these projects shed light on two post-colonial generations of writers and artists, their claims to the colonial past, identity politics about cosmopolitanism in the present, and struggles over cultural capital for the future.
Keywords: Casablanca; nostalgia; recollection; fragments d’imaginaire; phantasm; city; urban archeology; La Source du lion; cosmopolitanism; post-colonial